The Role of the Tri Pusat Pendidikan in Combating Cyberbullying in Adolescents - Saryono, Saryono; Astuti, Sari; Susi, Susi (LPPM STKIP Kusuma Negara, 2024)
Cyberbullying in adolescents involves strong emotional aspects, where emotional disturbances serve as crucial signals in these cases. This research aims to understand the role of the Tri Pusat Pendidikan in addressing cyberbullying in adolescents. A literature review approach was employed by gathering data from various sources such as articles, books, journals, documents, and websites, which were analyzed meticulously. The research findings indicate that cyberbullying in adolescents is a complex issue influenced by their emotions and moral values. When emotions are disturbed or moral values are low, cyberbullying can act as a trigger. Psychological support for adolescents who are frequent victims of cyberbullying becomes crucial as they may face difficulties in receiving love and communicating effectively. Effective preventive measures need to focus on character education rooted in moral values. To achieve this, collaboration between family, school, and society namely Tri Pusat Pendidikan is highly essential. Through this collaboration, it is hoped that adolescents can understand the importance of respecting others, avoiding bullying behavior, and using communication technology responsibly.